Fast fringe-field switching of vertically aligned liquid crystals between high-haze translucent and haze-free transparent states. Issue 10 (9th August 2018) - Choi, Tae-Hoon; Woo, Jae-Hyeon; Jeon, Byoung-Gyu; Kim, Jiung; Cha, Myoungsik; Yoon, Tae-Hoon
ABSTRACT: We report control of the haze value in a liquid crystal (LC) cell driven by a fringe electric field. When a fringe field is applied to a vertically aligned (VA) cell, a large spatial phase difference with a short grating period is induced in the LC layer. The average grating period of a VA cell driven by a fringe field is a quarter of the pitch of the interdigitated electrodes, which is half of the grating period of a VA cell driven by an in-plane field. Moreover, a sharper spatial phase profile is built around the edges of the interdigitated electrodes, which led to a high haze of 84.3% in the translucent state. The device was haze-free in the transparent state owing to the use of an LC layer without a polymer structure. To increase the haze value of the LC device while retaining a short response time, we developed an LC cell with crossed interdigitated electrodes where a large spatial phase difference is induced with little dependence on the azimuth angle. By applying a fringe electric field to a 20 μm thick LC cell using crossed interdigitated electrodes, we demonstrated a very high haze of 95.4% and a response time of less than 5 ms. Graphical Abstract: